(untitled) (Journal of the College of Basic Education, 2022)
The research deals with the study (Integration of Interior Design Elements), which is an analytical study of Internet cafe spaces, and this is due to the importance they represent to users of this type of space, and the importance it carries in transmitting information to users and the scientific benefit it provides, as well as it is considered a place for recreation and entertainment, so the research contained It consists of four chapters represented in the first chapter and includes the research problem, which is the lack of design ideas implemented by the specialists in the Internet café spaces, which led to weakness of the interior designs in these spaces. Search was in